The People's Republic of China and India: Commercial Policies in the Giants - Ganeshan Wignaraja (Asian Development Bank (ADB), 2011)
This paper analyses the link between commercial policies and exports through a comparative analysis of the Asian giants—the People's Republic of China (PRC) and India. While the PRC has surged ahead of India to dominate world manufactured exports, India has acquired competitive capabilities in skill-intensive services. Favorable initial conditions such as large domestic markets and low-cost productive labor have laid the foundations for the giants' export success. While the gradual switch to marketoriented commercial policies in the late 1970s drove trade-led growth in the giants, the PRC's reforms were swifter and more coordinated. It has introduced an open door policy towards foreign direct investment (FDI), actively facilitated technological upgrading through FDI, steadily liberalized a controlled import regime, ensured a competitive exchange rate, and concluded more comprehensive free trade agreements (FTAs) with Asia's developing economies. India has attempted to develop more effective commercial policies since 1991, especially to attract FDI and liberalize imports. Therefore, one might expect the gap in trade performance between the PRC and India to narrow over time. However, both giants face an uncertain world economic environment in the aftermath of the global financial crisis and future export success will depend on their evolving commercial policies. Critical issues that still to be resolved include how the giants will respond to the risk of protectionism, manage real exchange rates, promote the use of FTAs among businesses, and increase spending on infrastructure as well as research and development.
hdl:11540/2033
Keywords: F13; O24; O53; P33; 330; FTAs; free trade agreements; People's Republic of China; India; commercial policy; trade